2011
DOI: 10.1007/s12374-011-9172-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile Analysis of Hypoxia Responses in Arabidopsis Roots and Shoots

Abstract: Physiological and molecular adaptation mechanisms enable plants to improve their survival under harsh conditions, including low oxygen levels caused by flooding. When Arabidopsis was exposed to hypoxia, we observed hyponastic response, shoot elongation, leaf chlorosis, and inhibited growth. To understand this response, we used a specialized complementary DNA microarray from our laboratory to examine the time-dependent profiles of gene expression in Arabidopsis roots and shoots. From this, we identified 282 hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…NAD + regeneration from NADH is considered to be the most important function of the alcoholic fermentation pathway under oxygen restricted conditions [ 98 ]. An increased expression level of adh under hypoxic stress was also demonstrated in the roots of radish [ 99 ], poplar [ 63 ], and the cucumber genotype Zaoer, which has a high level of tolerance to flooding stress [ 52 ]. Relative expression levels of adh obtained for both cucumber accessions by qRT-PCR correspond to RNA-Seq results.…”
Section: Discussionmentioning
confidence: 99%
“…NAD + regeneration from NADH is considered to be the most important function of the alcoholic fermentation pathway under oxygen restricted conditions [ 98 ]. An increased expression level of adh under hypoxic stress was also demonstrated in the roots of radish [ 99 ], poplar [ 63 ], and the cucumber genotype Zaoer, which has a high level of tolerance to flooding stress [ 52 ]. Relative expression levels of adh obtained for both cucumber accessions by qRT-PCR correspond to RNA-Seq results.…”
Section: Discussionmentioning
confidence: 99%
“…MPK3/6 act in retrograde signaling following mitochondrial ROS stress during hypoxia (Chang et al, 2012) and activate ERF6 (a hub of immunity, ROS, and hormone responses; Huang et al, 2016) upon B. cinerea attack or ROS treatment (Meng et al, 2013). WRKY33 contributes to Arabidopsis resistance to B. cinerea (Liu et al, 2015) and submergence tolerance (Hwang et al, 2011).…”
Section: Erf-vii In Plant-pathogen Interactionsmentioning
confidence: 99%
“…However, still little is known of WRKY genes’ involvement in submergence tolerance in the model plant Arabidopsis thaliana to date, although several studies have indicated that hypoxia could change the expression of some WRKY genes and mutation of some WRKY genes can change the hypoxia sensitivity. For example, submergence can induce expression of WRKY22 , thereby enhancing disease resistance in Arabidopsis (Hsu et al ., 2013), while WRKY33 is reportedly induced after hypoxia treatment in Arabidopsis roots (Klok et al ., 2002) and the wrky33 mutant is hypersensitive to hypoxia stress treatment (Hwang et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%